1998
DOI: 10.1046/j.1365-2133.1998.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoxanthoma elasticum-like papillary dermal elastolysis: report of four Japanese cases and an immunohistochemical study of elastin and fibrillin-1

Abstract: We report four patients with pseudoxanthoma elasticum-like papillary dermal elastolysis (PDE). Multiple small papules on the neck, clinically resembling pseudoxanthoma elasticum, and loss of the elastic fibre network in the papillary dermis were found in each case. Immunohistochemical staining for elastin and fibrillin-1 in one patient demonstrated the disappearance of elastin and fibrillin-1 in the papillary dermis. Site-matched normal skins of the elderly showed intact elastin but a lack of fibrillin-1 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 12 publications
2
35
0
3
Order By: Relevance
“…A recent study using chimeric MT-MMPs demonstrated that the catalytic domains of MT1-and MT3-MMP, which are responsible for TIMP-2 binding, are major determinants for the lower efficiency of MT3-MMP in promoting pro-MMP-2 activation (67). Together, these observations suggest that under conditions of MT1-MMP and MT3-MMP co-expression in cells (35,68), activation of pro-MMP-2 is likely to proceed preferentially via the MT1-MMP/TIMP-2 axis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…A recent study using chimeric MT-MMPs demonstrated that the catalytic domains of MT1-and MT3-MMP, which are responsible for TIMP-2 binding, are major determinants for the lower efficiency of MT3-MMP in promoting pro-MMP-2 activation (67). Together, these observations suggest that under conditions of MT1-MMP and MT3-MMP co-expression in cells (35,68), activation of pro-MMP-2 is likely to proceed preferentially via the MT1-MMP/TIMP-2 axis.…”
Section: Discussionmentioning
confidence: 48%
“…MT3-MMP (MMP-16), which was originally cloned from human melanoma tissue and human placenta (30), is expressed in a variety of normal (30 -33) and tumor (7,(33)(34)(35) tissues. Studies with a purified active MT3-MMP lacking the transmembrane domain have shown that the truncated enzyme cleaves a variety of ECM components and is inhibited by TIMP-2 and TIMP-3 but not by TIMP-1 (29).…”
mentioning
confidence: 99%
“…8 Some authors explain the exclusive female predominance with the likelihood of women to seek medical care more often for cosmetic concerns. 5 The pathogenesis of PXE-like PDE is still obscure. It is mainly believed that it is related to ultraviolet radiation, intrinsic aging, or abnormal elastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathomechanistic details and the role of predisposing genetic factors are unknown. In papillary dermal elastolysis, white-yellow papules resembling PXE can be observed in aged women (60-80 years), although, in contrast to PXE, these lesions are histologically characterized by loss of elastin in the papillary dermis (Ohnishi et al, 1998). Moreover, elastic fibres similar to those of PXE have been observed in the lesional skin of patients with a variety of inflammatory skin diseases in the absence of clinical evidence of PXE (Bowen et al, 2007), in calcific elastosis, lipedema, lipodermatosclerosis, granuloma annulare, lichen sclerosus, morphea profunda, erythema nodosum, septal panniculitis, basal cell carcinoma and fibrosing dermatitis (Bowen et al, 2007;Taylor et al, 2004).…”
Section: Acquired Conditionsmentioning
confidence: 99%